Baggage Tracking and Handling by Rfid and Iot in Airports Using Nodemcu - M. Srinivasa Rao, V, Madhava Reddy, P.V.M. Vijaya Bhaskar, K.Sreenath (Mathematical Statistician and Engineering Applications, 2023)
An extremely well-liked pastime among people is travelling. and for long distances, most people choose to use airlines and carry luggage along with them when travelling. This luggage is taken care by the airlines once they’ve been checked-in at the airport. This segment of baggage handling is one of the vulnerable processes that may leads to missing of baggage. This missing baggage can be handled properly and safely in airports by using RFID and cloud. A baggage handling system is introduced in the airport at two stages i.e., at departure section and destination section of airport. These baggage's pass-through multiple sections in airport on a conveyor. Every section is attached with a RFID reader and every bag is attached with a RFID tag with information of traveler embedded in it. So whenever the bag is passed through any section the RFID receiver senses the information in RFID tag through radio waves and send the captured information to the cloud where the user can monitor the baggage.